Degradation of phenol in wastewater through an integrated dielectric barrier discharge and Fenton/photo-Fenton process - Niusha Kavian; Gholamreza Asadollahfardi; Ali Hasanbeigi; Mohammad Delnavaz; Amirmohsen Samadi (Ecotoxicology and Environmental Safety, 2024)
In this study, a non-thermal dielectric barrier discharge-Fenton/photo-Fenton process was investigated to remove phenol from synthetic wastewater. The changes and optimal values of influencing parameters, including treatment time, iron concentration, phenol initial concentration, and pH, were investigated based on the central composite design (CCD) method. The presence of 0.4 mmol/L of iron in the phenol solution with a concentration of 100 mg/L increased the removal efficiency and pseudo-first-order kinetic constant compared to dielectric barrier discharge cold plasma (DBDP) alone from 0.0824 min−1 and 56.8% to 0.2078 min−1 and 86.83%, respectively. The phenol removal efficiency was reduced to 52.9%, 45.6% and 31.8% by adding tert-butyl alcohol (TBA) with concentrations of 50, 100, and 200 mg/l, respectively. After 12 min of DBDP irradiation, the pH of the sample decreased from 5.95 to 3.42, and the temperature of the sample increased from 19.3 to 37.2 degrees Celsius. The chemical oxygen demand (COD) of the sample containing 100 mg/L phenol under plasma-Fenton/photo-Fenton irradiation decreased from 241 mg/L to 161 mg/L. Phenol removal efficiency after 10 min of treatment in the presence of 0.4 mmol/L of iron with the reactor volume of 50 mL was 87%, but the efficiency decreased to 76%, 47%, and 9% by increasing the volume to 100, 200, and 400 mL, respectively. Reducing the power led to a decrease in the removal efficiency from 56.8% for 100 W power to 10.8% for 40 W. The energy efficiency for 50% removal by DBDP and plasma-Fenton/photo-Fenton systems was 5.86×10−3 kWh/mg and 1.27×10−3 kWh/mg, respectively.